PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN DATAR KELAS IV SDN 04 KOTO BARU KABUPATEN DHARMASRAYA - Ratnawati; Yulia Darniyanti; Neri Setiani (STKIP Subang, 2023)
This research is motivated by the lack of creative and innovative learning media so that students find it difficult to understand the material presented by educators, efforts to overcome this problem are the need to develop animated video learning media that can attract students' attention because of attractive images and colors. This type of research is Research and Development (R&D) research using the ADDIE model which consists of several stages (Analyze, Design, Development, Implementation, and Evaluation). The test subjects were class IV students at SDN 04 Koto Baru. Data collection instruments use validity instruments, practicality instruments, and effectiveness instruments. The assessment instrument was validated by three validators namely content/material, media and language, then the practicality sheet was determined by the practitioner. The effectiveness of animated videos is determined from the learning outcomes of class IV students at SDN 04 Koto Baru using animated videos. The results of the validation carried out by three validators obtained an average validity value of 85% with a very valid category in the sense that the animated video for learning Mathematics is suitable for use by students. The results of the practicality value of the educator's response questionnaire obtained an average of 89.99% in the very practical category. The results of the practicality value of the student response questionnaire obtained an average of 90.56% in the very practical category, so that the teacher and student response questionnaire obtained an average of 90.27% in the sense that it was easy for students to use and time efficient. The results of the effectiveness value of 10 students who took part in learning using the media developed on the Flat Shape material stated that 90% complete was categorized as very effective so that it was easy to use and very efficient in terms of time.